AN ANALYSIS ON THE INFLUENCE OF AUDITOR’S QUALITY, AUDIT OPINION IN THE PREVIOUS YEAR, FIRM GROWTH, FIRM SIZE, AUDIT LAG, AND DEBT DEFAULT ON THE ACCEPTANCE OF GOING CONCERN OPINION WITH AUDIT SWITCHING AS MODERATING VARIABEL (A Study at Property and Real - Sari S, Indira Permata (International Journal of Public Budgeting, Accounting and Finance, 2018)
The title of the research was the Influence of Auditor’s Quality, Audit Opinion in the Previous Year, Firm Growth, Firm Size, Audit Lag, and Debt Default on Acceptance of Going Concern Opinion with Audit Switching as Moderating Variable (in Property and Real Estate Companies Listed in BEI or Indonesia Stock Exchange in the Period of 2009-2016). The objective of the research was to get empirical evidence on the influence of Auditor’s Quality, Audit Opinion in the Previous Year, Firm Growth, Firm Size, Audit Lag, and Debt Default on Acceptance of Going Concern Opinion with Audit Switching as Moderating Variable. The data were gathered by using purposive sampling technique in Property and Real Estate Companies Listed in BEI in the Period of 2009-2016. The samples were 29 Property and Real Estate Companies. The research used logistic regression analysis to analyze the data because independent variables were a metric and non-metric combination. The result of the research showed that (1) there was the influence of Auditor’s Quality, Audit Opinion in the Previous Year, Firm Growth, Firm Size, Audit Lag, and Debt Default on Acceptance of Going Concern Opinion, (2) partially, Auditor’s Quality, Audit Opinion in the Previous Year, Firm Growth, and Debt Default had the influence on Acceptance of Going Concern Opinion, while firm size and Audit Lag did not, (3) the result of absolute difference test showed that Audit Switching was not moderating variable.